ANALISIS DAMPAK PINJAMAN MODAL USAHA TERHADAP PENDAPATAN DAN LABA PEDAGANG DI PASAR BATUAH MARTAPURA - ZULKIFLI ZULKIFLI; NASRUDIN NASRUDIN (PPJP Universitas Lambung Mangkurat, 2019)
This study is done to know how the traders are felt after receiving credit venture capital loans and the extent of income and profits development of merchants at the market of taibah martapura after receiving investment capital loans from banks and from markets.The method used in this study is to describe comparatif descriptive and approach. The population in this study was that of merchants who used their own capital and who used venture capital from both banks and markets, as many as 30 people. The methods of sample taking use of purposive side methods. The amount of samples in the study of 30 people, the data being processed using Mann Whitney's U-Test test to see the comparison between the own capital and the borrowed capital.Studies show that differences in the income and profits levels of the traders undergo significant changes in self-use and after receiving business capital loans. Test result conduced with the mann Whitney u-test method using the SPSS indicate the output of statistical test, that the value of A sig. (2-tailed) in amount of 0.001, 0.000, 0.005 and 0.002 smaller than 0.05. Then it could be concluded that hypotheses are this acceoted that there is a dufference I income and profit between their own capital and borrowed capital.The biggest problem for business traders is their limited ability to invest. Keywords: income develoment, profit, capital loan